Business relationship network model from social reactions data - Tsutsumi, Diego Paolo (2019)
One of the primary ways to expand a business or to keep it stable during a crisis is to create partnerships with other companies. With that, this study presents results regarding a new data model, which explores user reactions on social media to indicate strategic business partnerships. There are three main contributions of this study to the literature: (i) a business relationship network model; (ii) a business community detection algorithm; and (iii) a business outlier detection algorithm; The evaluation of the contributions was performed exploring real data of approximately 280 million user reactions on Facebook. Contributing to the literature, this Master Thesis produced three full papers, one in the Journal of Internet Services and Applications (TSUTSUMI et al., 2019), and two in proceedings, Web Intelligence (TSUTSUMI; SILVA, 2018) and CoUrb (TSUTSUMI et al., 2018). Results suggest that business partnership recommendation is possible using the information available in social media.